Ad hoc Screen Translation in Soviet Estonian Film Clubs : Negotiating Boundaries - Hoffmann, Tiina (Journal of Audiovisual Translation, 2023)
In Soviet Estonian official cinemas, foreign films were always dubbed into Russian with Estonian subtitles. Founded at the end of the Thaw, film clubs and other semi-official screening locations became popular as part of the alternative scene and unauthorised discourse. They screened uncensored original Western European and Hollywood films and thus the works of forbidden film directors and cinema movements from the West were introduced to a limited audience of film enthusiasts. Compared to other Soviet Socialist Republics, Estonia was in a privileged geographical and linguistic position to be able to access the films of the West via Finland. Film clubs looked beyond the Iron Curtain and opened up a cultural dialogue between the West and Soviet Estonia. This article analyses the repertoire of foreign films and different translation modes, social relations and the agency of the interpreters, and it looks at their interpretative act from theoretical perspectives discussed by Juri Lotman and Naoki Sakai. Lay Summary: In the era of Soviet Estonia, where foreign films were typically re-edited and dubbed into Russian, film clubs emerged as underground screening locations that offered uncensored original Western European and Hollywood films. These clubs played a crucial role in introducing the works of forbidden film directors and cinematic movements from the West to a limited audience of film enthusiasts. Soviet Estonia stood out in three significant aspects: 1) it was the only SSR to subtitle all films in the official cinema into Estonian; 2) it had a vibrant film club culture in universities with diverse repertoires from Finland, and all films had a live translation into Estonian, 3) and it had access to Finnish television broadcasting Western movies that were otherwise not shown in the Soviet Union (Estonian and Finnish are closely related languages that share many semantic and grammatical structures). Compared to other Soviet Socialist Republics, Estonia had the advantage of its geographical and linguistic position, facilitating a socio-cultural dialogue with the West. The various translation methods employed, often conducted on an ad hoc basis, social dynamics, and the role of interpreters in the film clubs, played a transformative role in dismantling the barriers of the Iron Curtain. Interpreters, by navigating the boundaries between the original films and their translations, significantly influenced the understanding of Western cinema and culture in Soviet Estonia.